Pensando la globalización y la pandemia - Cordero, Jaime (2021)
Jaime Cordero (Perú) - Comentarista/autor; Gisella Hurtado Lenci (Perú) - Comentarista/autora; Oscar Sanchez Benavides (Perú) Moderador/autor